2014
DOI: 10.1162/jocn_a_00638
|View full text |Cite
|
Sign up to set email alerts
|

When Events Change Their Nature: The Neurocognitive Mechanisms Underlying Aspectual Coercion

Abstract: The verb ‘pounce’ describes a single, near-instantaneous event. Yet, we easily understand that, “For several minutes the cat pounced…” describes a situation in which multiple pounces occurred, even though this interpretation is not overtly specified by the sentence’s syntactic structure or by any of its individual words—a phenomenon known as ‘aspectual coercion’. Previous psycholinguistic studies have reported processing costs in association with aspectual coercion, but the neurocognitive mechanisms giving ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 40 publications
6
35
0
2
Order By: Relevance
“…This might manifest as a late sustained negativity effect, similar to that previously observed in association with complex semantic operations involving the maintenance, computation and/or selection of non-canonical event structure representations within working memory (e.g. Baggio, Van Lambalgen, & Hagoort, 2008; Bott, 2010; Paczynski, Jackendoff, & Kuperberg, in press). …”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…This might manifest as a late sustained negativity effect, similar to that previously observed in association with complex semantic operations involving the maintenance, computation and/or selection of non-canonical event structure representations within working memory (e.g. Baggio, Van Lambalgen, & Hagoort, 2008; Bott, 2010; Paczynski, Jackendoff, & Kuperberg, in press). …”
Section: Introductionsupporting
confidence: 66%
“…And, in a recent study, we observed a late-onset sustained negativity effect in association with iterative aspectual coercion, in which a punctive action (e.g. pounce) must be repeated for a period of time, specified by the preceding context (Paczynski, Jackendoff, & Kuperberg, in press). We will return to a more complete analysis of these studies in the Discussion section.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Outros experimentos também corroboram a hipó-tese da coerção iterativa utilizando diferentes métodos como rastreamento ocular (TOWNSEND, 2012), leitura auto monitorada (CHAN, 2013) e EEG (PACZYNSKI et al, 2014;YANO, 2016; BŁASZCZAK e KLIMEK-JANKOWSKA, a aparecer).…”
Section: Coerção Aspectualunclassified
“…Uma versão prévia também foi apresentada no congresso Scientiarum Historia VIII na UFRJ. KUPERBERG, 2014;YANO, 2016; BŁASZCZAK, KLIMEK-JANKOWSKA, a aparecer) e magnetoencefalografia (BRENNAN, PYLKKÄNEN, 2008). Visto que as propriedades em conflito no processamento deste tipo de sentença são conhecidas dos estudos do aspecto lexical (aktionsart) -a pontualidade do evento [pular] e a duratividade do contexto [por alguns minutos] -o fenômeno foi batizado com o nome Coerção Aspectual (PUSTEJOVSKY, 1995;JACKENDOFF, 1997).…”
unclassified